Ponudba in povpraševanje na licitacijah vrednejših lesnih sortimentov v Slovenj Gradcu - Kobal, Milan (Gozdarski vestnik, 2013)
Auctions of value wood assortments in Slovenia take place in Slovenj Gradec already for seven years (2007 - 2013). Auctions of value wood assortments are an established manner of value wood assortments sale in almost all European Union countries. The organizer prepares a catalogue of wood assortments on the basis of the supplied wood assortments and the buyers have a certain amount of time for inspecting wood assortments and handing in a written offer for every individual wood assortment. At seven Slovenian auctions of value wood assortments increasing amounts of wood assortments as well as increasing numbers of wood assortments vendors, buyers, and offers have been observed. The highest prices of the sold wood assortments are constantly increasing and are always reached by sycamore maple followed by common walnut. Also eastern black walnut and plum assortments are valued. Comparison of supplies of wood assortments and demand for wood assortments at auction of value wood assortments in Slovenia and at three auctions of value wood assortments in Austria in 2013 shows, that a larger number of wood assortments, larger volume of wood assortments and larger number of wood assortments vendors were present at Slovenian auction of value wood assortments. It would make sense to intensify promotional activities and thus attract even more vendors and buyers of value wood assortments in Slovenia and neighboring countries.
Keywords: gozdno-lesna veriga; licitacije; lesni sortimenti; vrednost; ocene; dodana vrednost; trženje